Abundance and spatio-temporal distribution of the amphidromous shrimp Macrobrachium olfersii (Caridea: Palaemonidae) along the Ribeira de Iguape River (Sao Paulo, Brazil) - Ribeiro, Crislene Cristo [UNESP]; Polachini Lopes, Victor Hugo [UNESP]; Bertini, Giovana [UNESP] (Soc Brasileira Carcinologia, 2020)
In this study we investigated the distribution of Macrobrachium olfersii (Wiegmann, 1836) along similar to 150 km of the Ribeira de Iguape river, Sao Paulo, Brazil. We compared the abundance and spatio-temporal distribution, and checked for differences in size and proportion of each sex in the collections, using two sampling methods. Shrimps were collected monthly at four sites (Eldorado, Sete Barros, Registro, and Iguape), from January to December 2007, using traps and sieves. We obtained a total of 23,818 individuals. The abundance was significantly higher at the Iguape-site, which was the closest to the estuary. There was a positive cross-correlation between abundance and rainfall, indicating an increase in abundance with a decrease in rainfall. The body size increased significantly upstream, suggesting a juvenile upstream migration, controlled by the rainfall regime and the amphidromous behavior of M. olfersii. More than 95% of the individuals were captured by sieving through the marginal vegetation of the river. The average size and sex ratio of each sample varied depending on the capture method: traps captured more and larger males than the sieve. Therefore, we recommend the combined use of these methods to obtain a better coverage of the population biology of freshwater shrimps.
Keywords: Capture method; rainfall; sieve; trap; Vale do Ribeira